A Low-Profile Dual-band Single-layer Multifunctional Metamaterial Based Frequency Selective Surface for 5G Applications - Bilal Ur Rehman; Kifayatullah Bangash; Humayun Shahid; Muhammad Amir; Muhammad Iftikhar (Pakistan Journal of Engineering & Technology)
A low-profile dual-band single-layer multifunctional metamaterial-based frequency selective surface for 5G applications is proposed. The proposed design is a modified disc shape structure with slots at the edges and symmetrical semi-circle apertures to get a broadband 3-dB passband of 29.6-36 GHz. The unit cell dimensions of the structure are 5 × 5 × 0.259mm and operate in the 5G range with pass-bands occurring at 31.75 GHz, 40.9 GHz, and stop-bands occurring at 26.125 GHz, 39.6 GHz showing polarization independence and incident angle stability from 0°- 45°. As a perfect absorber, its values are optimized to achieve almost unity absorption at 30.068 GHz. The proposed design is used to enhance the performance of a conventional microstrip patch 5G antenna by using a superstrate with a 5 × 5 array of the proposed unit cell. Appreciable improvement in gain and far-field broadband radiation properties of the patch antenna is achieved on top of subtle improvement reported in terms of operational bandwidth. The superstrates with an array of proposed frequency selective surface (FSS) can be used as radomes to protect the patch antenna. The proposed structure offers potential for deployment in modern-day applications such as sensor fusion systems, reflect arrays, and anti-reflective coatings.